(untitled) (Global Journal of Human-Social Science, 2013)
In dynamic assessment which emphasizes the process rather than product learners are provided with corrective feedback in categorized levels On the other hand Blog is an on-line and user-value driven technology widely used in language learning This study was an attempt to investigate the effect of the Web 2 0 on writing ability of Iranian EFL learners through the process of dynamic assessment To do so twenty low advanced EFL learners were randomly selected to take part in an eight-session class in advanced writing The participants were assigned into two control and experimental groups consisting of ten members Both groups were exposed to dynamic assessment however they differed in that the dynamic assessment of the experimental group was applied online through using a blog and the dynamic assessment of the control group was based on traditional paper-and-pencil method The quantitative data were analyzed through using a paired t-test and the answers to open-ended questions extracted from distributed questionnaires among the experimental group were analyzed qualitatively The results indicated that the use of blogs not only improved the writing ability of the learners but also facilitated the procedure of their writing assessment